Accelerated phase of chronic mylogenous leukemia in paediatric with metabolic acidosis and poor nutritional status. A case report - Riadi Wirawan Riadi Wirawan (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2005)
We reported a case of a twelve year old girl diagnosed as chronic myelogenous leukemia (CML), metabolic acidosis and poor nutrional status. The chief complaints were bulging abdomen, without abdominal pain, nausea and vomiting, accompanied by episodic pain in the lower extremities and buttocks without swelling or redness. Physical examination revealed hepatosplenomegaly, multiple lympadenopathy, body weight for age 54% of P50 and body weight for height 60% of P50; under P65. The laboratory findings were normochromic normocytic anemia, leucocytosis with shift to the left, myelocyte and neutrophil domination, thrombocytosis, hypercellular bone marrow with hyperactive granulopoiesis and megakaryocyte, erythropoiesis and NAP score decreased and the result of blood gas analysis was partially compensated metabolic acidosis with hypoxemia.Key words: Chronic myelogenous leukemia - metabolic acidosis - poor nutritional status - infection - hydroxyurea, cytosar